DNA Polymerase ɛ Deficiency Leading to an Ultramutator Phenotype: A Novel Clinically Relevant Entity. (May 2017) - Castellucci, Enrico; He, Tianfang; Goldstein, D. Yitzchak; Halmos, Balazs; Chuy, Jennifer
Abstract: Deficiencies in DNA repair due to mutations in the exonuclease domain of DNA polymerase ɛ have recently been described in a subset of cancers characterized by an ultramutated and microsatellite stable (MSS) phenotype. This alteration in DNA repair is distinct from the better‐known mismatch repair deficiencies which lead to microsatellite instability (MSI) and an increased tumor mutation burden. Instead, mutations in POLE lead to impaired proofreading intrinsic to Pol ɛ during DNA replication resulting in a dramatically increased mutation rate. Somatic mutations of Pol ɛ have been found most frequently in endometrial and colorectal cancers (CRC) and can lead to a unique familial syndrome in the case of germline mutations. While other key genomic abnormalities, such as MSI, have known prognostic and treatment implications, in this case it is less clear. As molecular genotyping of tumors becomes routine in the care of cancer patients, less common, but potentially actionable findings such as these POLE mutations could be overlooked unless appropriate algorithms are in place. We present two cases of metastatic CRC with a POLE mutation, both of which are ultramutated and MSS. The basic biochemical mechanisms leading to a unique phenotype in POLE deficiency as well as challenges faced with interpreting the genomic profiling of tumors in this important subset of patients and the potential clinical implications will be discussed here. The Oncologist 2017;22:497–502 Key Points: Clinicians should recognize that tumors with high tumor mutation burden and that are microsatellite stable may harbor a POLE mutation, which is associated with an ultramutated phenotype. Work‐up for POLE deficiency should indeed become part of the routine molecular testing paradigm for patients with colorectal cancer. This subset of patients may benefit from clinical trials where the higher number of mutation‐associated neoantigens and defect in DNA repair may be exploited therapeutically. Abstract : Two cases of metastatic colorectal cancer with a POLE mutation, both of which were ultramutated and microsatellite stable, are presented and discussed from the standpoint of the basic biochemical mechanisms leading to a unique phenotype in POLE deficiency, the challenges faced with interpreting the genomic profiling of tumors in this important subset of patients, and the potential clinical implications.